Pengembangan Ekonomi Desa Berkelanjutan melalui Model Lumintu: Studi pada Kawasan Ekowisata Kopi di Desa Sumberdem, Kabupaten Malang - Nugroho Suryo Bintoro; Nurman Fadjar Setiawan; M. Afif Khoiruddin (Pusat Riset dan Inovasi Nasional, 2026)
The development of rural economies based on locally superior commodities is an integral part of inclusive and sustainable development strategies. Sumberdem located in Wonosari Subdistrict, Malang Regency, possesses significant potential for the development of coffee-based ecotourism. However, this potential remains largely underutilized due to several structural and institutional constraints. Key challenges include inadequate supporting infrastructure, limited capacity of local human resources, and the absence of downstream processing for coffee products. This community engagement program implemented an adaptive approach known as the Lumintu model, rooted in the Participatory Rural Appraisal (PRA) framework. Field assessments revealed critical limitations such as poor road access to plantation areas, insufficient agricultural irrigation, and weak digital connectivity. Moreover, the capacity of village institutions—such as the Village-Owned Enterprises (BUMDesa) and coffee farmer groups—remained low, resulting in local coffee products with limited added value. The initial implementation of the program has shown promising results, particularly in strengthening institutional capacity through training on tourism business management and high–value coffee processing. Furthermore, product diversification through the development of coffee-based agrotourism and digital marketing innovations has been successfully introduced. Overall, this community engagement initiative has provided a concrete solution to rural development challenges in Sumberdem Village. Moving forward, the village is expected to strengthen its position as a sustainable coffee ecotourism destination and improve the long-term economic well-being of its residents. The proposed development model also holds the potential for adaptation and replication in other rural areas with similar characteristics, thereby supporting the broader achievement of the Sustainable Development Goals (SDGs).